2013
DOI: 10.3892/or.2013.2557
|View full text |Cite
|
Sign up to set email alerts
|

Key genes and pathways in thyroid cancer based on gene set enrichment analysis

Abstract: The incidence of thyroid cancer and its associated morbidity has shown the most rapid increase among all cancers since 1982, but the mechanisms involved in thyroid cancer, particularly significant key genes induced in thyroid cancer, remain undefined. In many studies, gene probes have been used to search for key genes involved in causing and facilitating thyroid cancer. As a result, many possible virulence genes and pathways have been identified. However, these studies lack a case contrast for selecting the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Hébrant et al (14) reported that a more marked EMT was the qualitative difference between PTC and ATC, by examining 11 ATC and 48 PTC samples in GSE33630. He et al (15) found that the p53 signaling pathway, which included 13 genes, was important for thyroid cancer using gene set enrichment and meta-analysis. Xu et al (16) selected the BCL2, MRPS31, ID4, RASAL2, DLG2, MY01B, ZBTB5, PRKCQ, PPP6C genes and an miscRNA on considering NT, ATC and PTC together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hébrant et al (14) reported that a more marked EMT was the qualitative difference between PTC and ATC, by examining 11 ATC and 48 PTC samples in GSE33630. He et al (15) found that the p53 signaling pathway, which included 13 genes, was important for thyroid cancer using gene set enrichment and meta-analysis. Xu et al (16) selected the BCL2, MRPS31, ID4, RASAL2, DLG2, MY01B, ZBTB5, PRKCQ, PPP6C genes and an miscRNA on considering NT, ATC and PTC together.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hébrant et al (14) found that ATC and PTC overlapped. He et al (15) analyzed 13 genes and one pathway associated with ATC. In addition, Xu et al found nine genes and one miscRNA, which were identified as candidates for the progression of thyroid cancer (16).…”
Section: Introductionmentioning
confidence: 99%
“…Our study thus identified a number of important pathways that were differentially expressed in FTC, some of which would be expected by the malignant profile of FTC compared to FTA. For example, the p53 signalling pathway plays an important role in cancer cell apoptosis and DNA repair by causing cycle arrest in response to DNA damage [37], and has been previously implicated in thyroid cancers [38]. Cell cycle progression is regulated and facilitated by cyclin-dependent kinases that are activated by cyclins such as cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…Our study thus identified a number of important pathways that were differentially expressed in FTC, some of which would be expected by the malignant profile of FTC compared to FTA. For example, the p53 signaling pathway plays an important role in cancer cell apoptosis and DNA repair by causing cycle arrest in response to DNA damage [57] and previously implicated in thyroid cancers [12]. Cell cycle progression is regulated and facilitated by cyclin-dependent kinases that are activated by cyclins such as cyclin D1.…”
Section: Discussionmentioning
confidence: 99%